Public-Private Collaboration on Productive Development in Uruguay - Lucía Pittaluga; Andrés Rius; Andrés Bianchi; Macarena González (Inter-American Development Bank (IDB), 2014)
The PPC for PDPs implemented in Uruguay in recent years have provided fertile ground for research. Many have achieved results that can be analyzed within the scope of their respective histories and institutional settings. The study inquires about what PPCs maximize the benefits of PDP results and minimizes rent-seeking behavior or the capture of government. In other words, it wants to disentangle how did the PPCs selected balanced these two apparently conflicting goals. The results show that some PPCs managed these matters better than others did. A history of private-public collaboration at the sectoral level was a key factor in understanding the different results. The imposition of foreign regulations to export-intensive sectors is another factor that reduces the imbalance. Additionally, the PPCs' degree of sophistication and the lower risk of one-sidedness depend on the capacities of public and private actors. Finally, the study found that the PPC design that most likely has better results has to be consistent with the kind of good, that is, the public, club, or private good, the PDP is providing.
hdl:11319/6405
Keywords: L52; O25; 330; Productive development policies; Public-Private collaboration; Uruguay; Meat traceability policy; Cluster promotion policy; Sectoral councils